2008
DOI: 10.1158/0008-5472.can-07-6517
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gastric Cancer Invasion and Metastasis by PLA2G2A, a Novel β-Catenin/TCF Target Gene

Abstract: Elevated expression of the PLA2G2A phospholipase in gastric cancer (GC) is associated with improved patient survival. To elucidate function and regulation of PLA2G2A in GC, we analyzed a panel of GC cell lines. PLA2G2A was specifically expressed in lines with constitutive Wnt activity, implicating B-catenin-dependent Wnt signaling as a major upstream regulator of PLA2G2A expression. The invasive ability of PLA2G2A-expressing AGS cells was enhanced by PLA2G2A silencing, whereas cellular migration in non-PLA2G2A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 32 publications
6
68
0
Order By: Relevance
“…However, there was no significant difference in the mobility of AGS cells stably transfected with HSulf-1 and control cells. In accordance with these observations, we found that mRNA levels of metastasis-related genes, such as DKK1, MMP-2, S100A4, and S100P, (22,(28)(29)(30) were downregulated in HSulf-1 transfected MKN28 cells, but that there were no noticeable change in the expression of these genes in AGS cells (Fig. 2d).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, there was no significant difference in the mobility of AGS cells stably transfected with HSulf-1 and control cells. In accordance with these observations, we found that mRNA levels of metastasis-related genes, such as DKK1, MMP-2, S100A4, and S100P, (22,(28)(29)(30) were downregulated in HSulf-1 transfected MKN28 cells, but that there were no noticeable change in the expression of these genes in AGS cells (Fig. 2d).…”
Section: Resultssupporting
confidence: 85%
“…(17) Dysregulation of the Wnt signaling pathway has been implicated in gastric carcinogenesis and metastasis. (22,23,(31)(32)(33) Therefore, in the present study, we first assessed the expression profile of Wnt pathway genes in AGS and MKN28 cells. As shown in Figure 3(a), the expression of several Wnt ligands was elevated in both cell lines (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cby was first identified as an interactor with b-catenin in humans, which suggested it could be a tumor suppressor gene [204] . Silencing of PLA2G2A (phospholipase A2) enhances the invasive ability of gastric cancer cells [205] . Surprisingly, PLA2G2A, which is an independent predictor of favorable outcome for patients with gastric cancer [206,207] , is also a direct Wnt target gene and it has been found upregulated in early stages of gastric cancer.…”
Section: Wnt/b-catenin Signaling and Metastatic Potential In Gastric mentioning
confidence: 99%
“…Surprisingly, PLA2G2A, which is an independent predictor of favorable outcome for patients with gastric cancer [206,207] , is also a direct Wnt target gene and it has been found upregulated in early stages of gastric cancer. Ganesan et al [205] have proposed that in late-stage tumors, Wnt signaling is still active driving expression of protooncogenes; however, PLA2G2A expression is decreased possibly by epigenetic inactivation and/or genomic deletions, resulting tumors with a highly aggressive clinical phenotype. Moreover, the overexpression of the Wnt signalling regulator sFRP1 has been correlated with activation of TGFb signalling pathway, thereby it may induce cell proliferation, EMT and invasion [130] .…”
Section: Wnt/b-catenin Signaling and Metastatic Potential In Gastric mentioning
confidence: 99%